Transport properties of resistive switching in Ag/Pr0.6Ca0.4MnO3/Al thin film structures - Lähteenlahti V.; Schulman A.; Huhtinen H.; Paturi P. (ELSEVIER SCIENCE SA, 2022)
Thin films of Pr0.6Ca0.4MnO3 were prepared by pulsed laser deposition with an asymmetric pair of Ag and Al metal electrodes in order to study their resistive switching properties. The devices exhibited stable voltage controlled bipolar switching which proved to be reliable and non-volatile. The resistive states show a well-defined dependence on the write voltage, which was used to achieve several intermediate states, indicating that the devices could be utilized in hardware implementations of neuromorphic computing. The switching mechanism was attributed to the electric-field assisted migration of oxygen vacancies at the Al-electrode interface, resulting in a formation and modulation of a rectifying interfacial AIO(x) layer. The current-voltage characteristics were analyzed by means of the power exponent representation, which hinted to a device state dependent interplay of bulk-limited Poole-Frenkel conduction and interface-limited Schottky conduction. A deeper understanding of resistive switching characteristics in Ag/Pr0.6Ca0.4MnO3/Al will lead towards further advances in manganite-based neuromorphic circuits. (C) 2019 The Authors. Published by Elsevier B.V.